The 2008 financial crisis and the Renminbi internationalization: A crise financeira de 2008 e a internacionalização do Renminbi - de Sousa, Ana Tereza Lopes Marra; de Freitas, William Daldegan (Conjuntura internacional, 2018)
In this work, we investigated the RMB internationalization. We have argued that the 2008 crisis had an important role to change the parameters of RMB internationalization policy. In the early 2000s that policy was pursued as an instrument to accelerate China's financial liberalization, but from the 2008 crisis onwards, the policy also took the responsibility of boosting Chinese foreign trade, facilitating the export of capital and increasing China's economic influence in the world. We have interpreted that the goal of the internationalization policy is not for RMB to replace the Dollar's role, but to route a future in which China's financial and monetary influence in the world will be bigger, making the country less dependent of United States (US) currency and financial system.